Prognozirovanie sportivnych dostiženij u grebcov-kanoistov vysšej kvalifikacii s pozicii skorosti ich postnagruzocnogo vosstanovlenija - Tomilin, K. G.; Kalinkin, L. A.; Ivanov, I. V.; Morozov, V. N.; Rostovtsev, V. L. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The purpose of this study is to determine the rational pedagogical instruction that forms the rational motor systems of athletes when controlling movements of a speed-power nature. The "information frames" of the introductory material for student-athletes were worked out. A survey of 600 athletes (International level, III athletics category) Revealed 10-15 variants of propulsion systems using the maximization of "strength", "speed", "height" (amplitude), "acceleration", "sharpness". The best results were noted when using instructions in 2-3 components, using the terms "speed", "height", "power", "acceleration". Changes occurred on the final result, a number of important biomechanical indicators, as well as the structure of the sports movement (which was confirmed by a change in the structure of reliable correlation links between the recorded indicators).